ATP6V0C Is Associated With Febrile Seizures and Epilepsy With Febrile Seizures Plus - Tian, Yang; Zhai, Qiong-Xiang; Li, Xiao-Jing; Shi, Zhen; Cheng, Chuan-Fang; Fan, Cui-Xia; Tang, Bin; Zhang, Ying; He, Yun-Yan; Li, Wen-Bin; Luo, Sheng; Hou, Chi; et al. (Frontiers in Molecular Neuroscience, 2022)
Purpose To identify novel genetic causes of febrile seizures (FS) and epilepsy with febrile seizures plus (EFS+). Methods We performed whole-exome sequencing in a cohort of 32 families, in which at least two individuals were affected by FS or EFS+. The probands, their parents, and available family members were recruited to ascertain whether the genetic variants were co-segregation. Genes with repetitively identified variants with segregations were selected for further studies to define the gene-disease association. Results We identified two heterozygous ATP6V0C mutations (c.64G > A/p.Ala22Thr and c.361_373del/p.Thr121Profs*7) in two unrelated families with six individuals affected by FS or EFS+. The missense mutation was located in the proteolipid c-ring that cooperated with a-subunit forming the hemichannel for proton transferring. It also affected the hydrogen bonds with surround residues and the protein stability, implying a damaging effect. The frameshift mutation resulted in a loss of function by yielding a premature termination of 28 residues at the C-terminus of the protein. The frequencies of ATP6V0C mutations identified in this cohort were significantly higher than that in the control populations. All the six affected individuals suffered from their first FS at the age of 7–8 months. The two probands later manifested afebrile seizures including myoclonic seizures that responded well to lamotrigine. They all displayed favorable outcomes without intellectual or developmental abnormalities, although afebrile seizures or frequent seizures occurred. Conclusion This study suggests that ATP6V0C is potentially a candidate pathogenic gene of FS and EFS+. Screening for ATP6V0C mutations would help differentiating patients with Dravet syndrome caused by SCN1A mutations, which presented similar clinical manifestation but different responses to antiepileptic treatment.